Breaking the Paradox of Innovation in Small Businesses through Sustaining and Disruptive Reinvention - V. Baard; T. Watts (Australasian Accounting, Business and Finance Journal, 2007)
In 2005 Deloitte Research released a paper examining the phenomenon they refer to as the ‘innovation paradox’: the inability or reluctance of manufacturing firms to pursue strategies that build the operational capabilities necessary for innovation that will provide both profitability and growth. The report claims that this is due to the rapidly increasing complexity of global markets and the lack of synchronising innovation efforts across their value chain, thus positioning the problem as an important contemporary issue. While the research did not specifically target small and medium enterprises, the implications for this business sector are considerable given their substantial contribution to global economies and their high failure rates in the first three to five years of operation. While not questioning the data in the Deloitte research, this paper does question the assumption that the phenomenon is irreversible and the apparent underlying self-fulfilling prophecy with respect to small to medium enterprises. To demonstrate this the authors draw on a case study of a small manufacturing company in rural New South Wales, Australia, which operated between 1889 and 1983, to show that the breaking of the innovation paradox was successfully achieved by this firm in the late nineteenth and early twentieth century. Applying the case study to the Deloitte model the study demonstrates contemporary similarities by overlaying the Laycock history on the successes / failures identified by Deloitte.
Keywords: Small business; reinvention; innovation paradox; Deloitte model